Within and combined season prediction models for perennial ryegrass biomass yield using ground- and air-based sensor data - Nguyen, Phat T.; Shi, Fan; Wang, Junping; Badenhorst, Pieter E.; Spangenberg, German C.; Smith, Kevin F.; Daetwyler, Hans D. (Frontiers in Plant Science, 2022)
Across-season biomass assessment is crucial in the cultivar selection process to accurately evaluate the yield performance of lines under different growing conditions. However, it has been difficult to have an accurate, reliable and repeated fresh biomass (FM) estimation of large populations of plants in the field without destructive harvesting, which incurs significant labour and operation costs. Sensor-based phenotyping platforms have advanced in the data collection of structural and vegetative information of plants, but the developed prediction models are still limited by low correlations at different growth stages and seasons. In this study, our objective was to develop and validate the global prediction models for across-season harvested fresh biomass (FM) yield based on the ground and air-based sensor data including ground-based LiDAR, ground-based ultrasonic and air-based multispectral camera to extract plant volume, density, height and Normalized Difference Vegetative Index (NDVI). The study was conducted in a row-plot field trial with 480 rows (3 rows in a plot per cultivar) throughout the whole 2020 growing season up to the reproductive stage. We evaluated the performance of each plant parameter, their relationship and the best subset prediction models using statistical stepwise selection at the row and plot level through the seasonal and combined seasonal datasets. The best performing model – FM ~ LV*LV_Den*NDVI had a determination of coefficient R2 of at least 0.9 in vegetative stages and 0.8 in the reproductive stage. Similar results can be achieved in a simpler model with just two LiDAR variables - FM ~ LV*LV_Den. In addition, LV and LV_Den showed a robust correlation with FM on their own over seasons and growth stages, while NDVI only performed well in some seasons. The simpler model based on only LiDAR data can be widely applied over season without the need of additional sensor data and may thus make the in-field across-season biomass assessment more feasible and practical for fast and cost-effective development of higher biomass yield cultivars.